Optimization of High-Performance-Concrete properties containing fine recycled aggregates using mixture design modeling (Fracture and Structural Integrity, 2021)
This investigation means to predict and modeling the fresh and hardened concrete behavior containing fine aggregates from concrete and brick wastes, for different recycled aggregates substitution rates.To succeed this, the design of experiments DOE method was used. It is observed that slump of recycled concrete is significantly influenced by the content in recycled concrete aggregates (RCA), natural sand (NS) and recycled brick aggregates (RBA), respectively.The compressive strength (CS) reaches a maximum value of 83.48 MPa with factors values of 25% RBA, and 75% RCA. And HPC’s based on RBA sand presented greater values of flexural strength at 7 days than HPC’s based on RCA sand, it was revealed that this is due to the RBA fines pozzolanic reaction and the production of new CSHs, which leads to better cement matrix densification.Under optimal conditions, themaximum desirability is 0.65, who has given HPC no added natural sand, by mixing recycled sands RBA (9.5%) with RCA (90.5%).The statistical terms result show that the expected models are very well correlated with the experimental data and have shown good accuracy.
Keywords: High performance concrete; Recycled aggregates; Mixture design modelling; Physico-mechanical properties; Optimization